مقارنة تأثير أنواع ومستويات مختلفة من الأسمدة العضوية والمعدنية في بعض صفات العنب الحلواني - سليمان, وردة محسن; ابراهيم, دعد معين (Latakia University Journal -Biological Sciences Series, 2016)
جرى هذا البحث خلال موسم 2012-2013على شجيرات عنب من الصنف الحلواني ، بعمر 10 سنوات ، مطعمة على الأصل41B. وذلك باستعمال ثلاثة مستويات من الأسمدة العضوية (سماد الأبقار، الأغنام، الدواجن) (10-20-40 طن/هـ) ، إضافةً إلى ثلاث معاملات من خلطة من هذه الأسمدة من المستويات الثلاثة ، وبواقع (3.33-6.67-13.33 طن/ه) من كل نوع سماد عضوي ، كما استعملت ثلاث معاملات للتسميد المعدني (N,P,K) من خلطة من الأسمدة الثلاث بنسبة (1:1:1) ، باستخدام الأسمدة المعدنية (يوريا 46%، سوبر فوسقات مركز 46%، سلفات البوتاسيوم 50%) بواقع (100-200-400 كغ/ه) إضافةً إلى الشاهد بدون تسميد ، وذلك لدراسة تأثيرها في بعض الصفات الكمية والنوعية لصنف العنب الحلواني وكانت النتائج كما يلي: حقق استعمال التسميد المعدني والعضوي بجميع مستوياته وأنواعه تفوقاً في جميع الصفات المدروسة مقارنة مع الشاهد. تفوقت أغلب مستويات التسميد العضوي وخلائطه على التسميد المعدني في جميع الصفات المدروسة. أعطى المستوى الأول من سماد الأغنام (10طن/ه) أفضل النتائج في وزن العنقود وكمية الإنتاج، في حين حقق المستوى الأول من سماد الدواجن أفضل النتائج في وزن 100 ثمرة. إن استعمال التسميد العضوي كان ذا تأثير إيجابي في تلون ثمار العنب،وتفوق على التسميد المعدني. ازداد إنتاج شجرة العنب على نحوٍ معنوي من 65.77 إلى 118.5 و97.8 كغ/شجيرة ، عند استعمال المستوى الأول من سماد الأغنام ، وخليط المستويات الثانية من الأسمدة المعدنية على التوالي. This research was carried out through the 2012-2013 season on 10 years old, grafted on the rootstock B41,grapevines of Al-Hulwani cultivar. Three levels (10,20,40 t/ha) of organic fertilizers of cow, sheep plus and poultry were used, in addition to three treatments from mixture of this levels (3.33,6.66,13.32 t/ha) for one type of the fertilizers. The research also included three treatments from mixture of mineral fertilization with (N,P,K) at the rate (1:1:1) by using urea 46%, super phosphate 46% and potassium sulphate 50% in three levels (100-200-400 kg/ha), in addition to the control without fertilization, to study their effects on Some quantitative and qualitative Characteristics of the grapevine cultivar Al-Hulwani. The results showed the following: The use of organic and mineral fertilization gave in all levels and types superiority in all studied characteristics compared to the control. Most levels of organic fertilization and its treatments are superior to mineral fertilization in all studied characteristics. The first level of sheep plus (10 kg/ha) gave the better results in weight of cluster and quantity of product, but the first level of poultry gave the better results in weight of 100 fruits. The use of organic manure was with positive effect on fruits color and was superior to mineral fertilization. The yield/vine increased significantly from 65.77kg/vine to 118.5 and 97.8kg/vine when the low level of sheep puls the mixture of the medium levels of mineral fertilizers were used.